Development of a Multicellular 3D Tumor Model to Study Cellular Heterogeneity and Plasticity in NSCLC Tumor Microenvironment - Arora, Leena; Kalia, Moyna; Dasgupta, Suman; Singh, Navneet; Verma, Anita K.; Pal, Durba (Frontiers in Oncology, 2022)
Heterogeneity is a characteristic feature of solid tumors. Intra-tumor heterogeneity includes phenotypic diversity, epigenetic abnormalities, cell proliferation, and plasticity that eventually drives disease progression. Studying tumor heterogeneity in 2D culture is challenging as it cannot simulate the microenvironmental features, such as hypoxia, nutrient unavailability, and cell-ECM interactions. We propose the development of multicellular (tri-culture) 3D spheroids using a hanging drop method to study the non-tumorigenic (BEAS-2B) vs. tumorigenic NSCLC (A549/NCI-H460)cells’ interaction with lung fibroblasts (MRC-5) and monocytes (THP-1). Unlike the non-tumorigenic model, the tumorigenic 3D spheroids show significant induction of cell proliferation, hypoxia, pluripotency markers, notable activation of cancer-associated fibroblasts, and tumor-associated macrophages. CD68+ macrophages isolated from tumorigenic spheroids exhibited profound induction of phenotypic endothelial characteristics. The results are zebrafish tumor xenograft model and by using human patient samples. This multicellular 3D tumor model is a promising tool to study tumor-stroma interaction and cellular plasticity, targeting tumor heterogeneity, and facilitating cancer therapy success against NSCLC.